Pequi Fruit Extract Increases Antioxidant Enzymes and Reduces Oxidants in Human Coronary Artery Endothelial Cells - Karla M. S. Braga; Eugenio G. Araujo; Frank W. Sellke; M. Ruhul Abid (MDPI AG, 2022)
Reactive oxygen species (ROS) imbalance results in endothelial cell function impairment. Natural phenolic antioxidant compounds have been investigated as therapeutic alternatives. The fruit bark of Brazilian-native pequi (Caryocar brasiliense, Camb.) is rich in polyphenols. The HPLC-MS (High-Performance Liquid Chromatography coupled with Mass Spectrometry) analyses identified gallic acid and catechin in six out of seven ethanolic extract samples prepared in our lab. In this study, we examined the effects of ethanolic pequi extract on ROS levels in human coronary artery endothelial cells (HCAEC) subjected to hypoxia or oxidative stress. We first confirmed the oxidant scavenging capacity of the extract. Then, HCAEC pre-incubated with 10 or 25 μg/mL of extract were subjected to hypoxia for 48 h or 100 μM H2O2 for six hours and compared to the normoxia group. Total and mitochondrial ROS levels and cell proliferation were measured. Pequi significantly reduced cytosolic HCAEC ROS levels in all conditions. Mitochondrial ROS were also reduced, except in hypoxia with 10 μg/mL of extract. HCAEC proliferation increased when treated with 25 μg/mL extract under hypoxia and after H2O2 addition. Additionally, pequi upregulated oxidative stress defense enzymes superoxide dismutase (SOD-)1, SOD-2, catalase, and glutathione peroxidase. Together, these findings demonstrate that pequi bark extract increases antioxidative enzyme levels, decreases ROS, and favors HACEC proliferation, pointing to a protective effect against oxidative stress.